11 и 13
Пошаговое объяснение:
а+в=24
а²-в²=48
а²-в²=(а+в)(а-в)⇒48=24(а-в)
а-в=2⇒а=2+в
а-в=2
в+в+2=24
2в=22
в=11
а=2+в=2+11=13
Привет!)
Пусть заданы числа а и b:
(1) --> a=24-b
(24-b)²-b²=48
576-48b+b²-b²=48
-48b=48-576
-48b=-528
b=11
a=24-11=13
ответ: 13 и 11
11 и 13
Пошаговое объяснение:
а+в=24
а²-в²=48
а²-в²=(а+в)(а-в)⇒48=24(а-в)
а-в=2⇒а=2+в
а+в=24
а-в=2
в+в+2=24
2в=22
в=11
а=2+в=2+11=13
Привет!)
Пусть заданы числа а и b:
(1) --> a=24-b
(24-b)²-b²=48
576-48b+b²-b²=48
-48b=48-576
-48b=-528
b=11
a=24-11=13
ответ: 13 и 11